Tổng hợp một số dẫn xuất của 1(2’,3’,4’,6’-tetra-o-acetyl--D-glucopyranosyl)-3-(4’’,6’’-diarylpyrimidine-2’’-yl)-thiourea - Thành và cộng sự, Nguyễn Đình (Vietnam Journal of Chemistry, 2014)
Some compounds of 1-(2’,3’,4’,6’-tetra-O-acetyl-b-D-glucopyranosyl)-3-(4”,6”-diarylpyrimidine-2’-yl)thioureas have been synthesized from corresponding isothiocyanates and 2-amino-4,6-diarylpyrimidines using two different synthetic methods. The hydrolysis of these acetated thioureas leads to form the corresponding deacetyled thioureas. Their spectroscopic properties have been studied.